Volunteer Retention in Prosocial Venturing: The Role of Emotional Connectivity - Farny, Steffen; Kibler, Ewald; Hai, Solange; Landoni, Paolo (Entrepreneurship Theory and Practice, 2019)
This study develops an understanding of the role of emotional connectivity for volunteer retention in prosocial business venturing. By embedding it in organizational ambivalence theory, our analysis of four volunteer-dependent community ventures reveals two mechanisms through which entrepreneurs strengthen volunteers’ emotional connectivity. We first identify emotion-focused practices that form volunteers’ emotional attachment to the venture, and then demonstrate how duality-focused practices, in the form of managing inherent organizational duality, complement emotion-focused practices to foster volunteers’ emotional loyalty to the venture. Theorizing from our findings, we introduce a model of managing volunteers’ emotional connectivity, and conclude by discussing its implications for prosocial venture research on volunteerism and affective commitment.